Early Cinema in Lithuania: The Emergence of a Cultural Tradition - Paškauskas Juozapas (Meno Istorija ir Kritika, 2022)
Leaning on the notions of transnationalism of cinema or Cinema of Small States, this article sets out to evaluate early cinema in the Northwestern Krai of the late 1800s–early 1900s Russian Empire and the region’s largest city, Vilnius, thematically, rather than chronologically, through the layers of the formation of film culture and the transformation of cinema into an aesthetic object. Such an approach presents a culturally new possibility of finding commonalities, allowing one to see early cinema in the provinces not necessarily as an always-late phenomenon that highlights the provinciality of the provinces, but on the contrary, as part of the overall European film tradition. This is argued from several aspects. Firstly, by showing how the perception of cinema has changed (and how this change coincided with Western trends) from cinema of attractions to narrative cinema; and secondly, by identifying changes in the repertoire of cinemas and in the established preferences of the early cinema audiences.